Implementation of Interactive Learning Media on the Blood Circulatory System Towards Science Literacy - Febryanie, Nina; Hafizah, Ellyna; Istyadji, Maya (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2025)
Scientific literacy is an important indicator in the implementation of science education, which must be integrated systematically at all levels of education. This study aims to investigate the differences in scientific literacy skills between classes taught using interactive learning media and those taught using conventional learning media, with a focus on the sub-topic of the circulatory system. Additionally, it aims to assess the changes in scientific literacy skills before and after the use of interactive learning media on the sub-topic of the circulatory system. The type of research employed was quasi-experimental, utilising a non-equivalent control group design with data collection techniques that included pretests and posttests of scientific literacy. These tests were used to evaluate the hypothesis through independent sample t-tests and paired sample t-tests. The study's results showed differences in scientific literacy abilities between classes taught using interactive learning media and those taught using conventional learning media in the sub-material of the circulatory system. The results of this study also indicated a difference in scientific literacy skills before and after the use of interactive learning media in the sub-material of the circulatory system. This study demonstrates that the use of interactive learning media that present content related to scientific phenomena can enhance students' scientific literacy skills. This research highlights the importance of utilising interactive learning media for teachers in enhancing students' scientific literacy.